Education of lower secondary mathematics teachers in Denmark and France - Winsløw, Carl; Durand-Guerrier, Viviane (NOMAD Nordic Studies in Mathematics Education, 2007)
This paper presents a comparative study of two surprisingly different systems of preparing teachers for lower secondary level teaching of mathematics, namely those of Denmark and France. We first describe these systems differences succinctly. The main part of the paper reports on a qualitative study of how final year teacher students in the two countries handle two hypothetical situations of mathematics teaching. Then we discuss how the findings could be related to the systems of formation described first.